P271 DOES SENILITY AFFECT THE MANIFESTATION AND MANAGEMENT OF PULMONARY EMBOLISM? EXPERIENCE OF AN ED. (18th May 2022) - Savioli, G; Lapia, F; Fumoso, F; Brattoli, M; Mugellini, A; Martignoni, A; Ceresa, I; Muzzi, A; Novelli, V; Preda, L; Lava, M; Maggioni, P; et al.
Abstract: Premises: Acute pulmonary embolism is a pathology characterized by high mortality. The elderly population is destined to increase, becoming, according to some authors, 30% of the population in the developed countries. Purpose of the Study: see if and how, in the real life of an Emergency Department, age can affect the manifestation (more severe or milder forms of pulmonary embolism; typical symptoms and atypical symptoms), patient management and adherence to guidelines. We considered subjects over 75 years of age to be elderly, as per the latest indications of the guidelines. Methods: Single–center retrospective observational study on all patients who entered our ED, where they received a diagnosis of acute PE. Enrollment began in 2016 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagostic / therapeutic algorithm, both for the risk of PE (Wells, Geneva and YEARS), and for the presentation of the risk of mortality at 30 days (sPESI). We analyzed the hospitalization rate, in–hospital mortality rate, the hospitalization rate in resuscitation and the length of hospitalization. We then analyzed adherence to the guidelines valid in the period under study. Results: We enrolled 487 patients, with equal gender distribution (F = 52%). 247 were older than 75 (50.7%). Age has a positive correlation with the presence of massive pulmonary embolism, in a statistically significant way (p < 0.05), and with the presence of organ damage, touching on statistical significance (p = 0.05). On the other hand there is no statistically significant difference in the prevalence of typical or atypical symptoms in the two groups. The vital parameters were instead comparable in the two groups with no statistically significant difference (p > 0.05). Long–term outcomes such as mortality, need for hospitalization, ICU stay and length of stay in hospital are also comparable results without statistically significant difference (p > 0.05). Adherence to international guidelines is also comparable between the two groups (p > 0.05). Conclusions: The study suggests that age correlates with more severe forms of pulmonary embolism but does not affect either patient management or short–term outcomes.